Engineering and living systems: Interfaces and opportunities - Rutsein, David D. (The Massachusetts Institute of Technology, 1970)
This book supplements existing medical programs with a new research approach to increase fundamental knowledge, and points the way to better medical care through more efficient application of engineering, technology, and systems development..